Data Set for the Reporting of Carcinomas of the Vulva: Recommendations From the International Collaboration on Cancer Reporting (ICCR). (10th November 2022) - Hoang, Lynn; Webster, Fleur; Bosse, Tjalling; Focchi, Gustavo; Gilks, C. Blake; Howitt, Brooke E.; McAlpine, Jessica N.; Ordi, Jaume; Singh, Naveena; Wong, Richard Wing-Cheuk; Lax, Sigurd F.; McCluggage, W. Glenn
Abstract : A cogent and comprehensive pathologic report is essential for optimal patient management, cancer staging, and prognostication. This article details the International Collaboration on Cancer Reporting (ICCR) process and the development of the vulval carcinoma reporting data set. It describes the "core" and "noncore" elements to be included in pathology reports for vulval carcinoma, inclusive of clinical, macroscopic, microscopic, and ancillary testing considerations. It provides definitions and commentary for the evidence and/or consensus-based deliberations for each element included in the data set. The commentary also discusses controversial issues, such as p16/human papillomavirus testing, tumor grading and measurements, as well as elements that show promise and warrant further evidence-based study. A summary and discussion of the updated vulval cancer staging system by the International Federation of Obstetricians and Gynaecologists (FIGO) in 2021 is also provided. We hope the widespread implementation of this data set will facilitate consistent and accurate reporting, data collection, comparison of epidemiological and pathologic parameters between different populations, facilitate research, and serve as a platform to improve patient outcomes.